1) X1 = 13, X2 = -15
2) X1 = 6, X2 = 1
3) X1 = 1, X2 = -2006
Объяснение:
1) x²+2x-195=0
a =1, b =2, c = -195
D = b²-4ac
D = 4-4·1·(-195) = 4+780 = 784
D>0, 2 корня
X1/2 = = = X1 = 13, X2 = -15
2) 3x²-7x+2=0
a = 3, b = -7, c = 2
D = (-7)²-4·3·2 = 25
X1/2 = = = X1 = 6, X2 = 1
3) x²+2005x-2006=0
a = 1, b = 2005, c = -2006
D = 2005²-4·1·(-2006) = 4.028.049
X1/2 = = = X1 = 1, X2 = -2006
10-4(2x+5)=6y-13
4y-63=5(4x-2y)+2
4y-63-20x+10y-2=0
14y-65-20x=0
x=0.7y-3.25
3-8x-6y=0
3-8*(0.7y-3.25)-6y=0
3-5.6y+26-6y=0
29-11.6y=0
y=29/11.6y=2.пятых
14*2.5-65-20x=0
-30-20x=0
x=-30/20
x=-1.5
1) X1 = 13, X2 = -15
2) X1 = 6, X2 = 1
3) X1 = 1, X2 = -2006
Объяснение:
1) x²+2x-195=0
a =1, b =2, c = -195
D = b²-4ac
D = 4-4·1·(-195) = 4+780 = 784
D>0, 2 корня
X1/2 =
=
= X1 = 13, X2 = -15
2) 3x²-7x+2=0
a = 3, b = -7, c = 2
D = b²-4ac
D = (-7)²-4·3·2 = 25
D>0, 2 корня
X1/2 =
=
= X1 = 6, X2 = 1
3) x²+2005x-2006=0
a = 1, b = 2005, c = -2006
D = b²-4ac
D = 2005²-4·1·(-2006) = 4.028.049
D>0, 2 корня
X1/2 =
=
= X1 = 1, X2 = -2006